Advancing Peptide-Based Vaccines Against Candida: A Comparative Perspective on Liposomal and Synthetic Formulations - Xin, Hong (Journal of fungi (Basel), 2025)
The growing threat of multidrug-resistant fungal pathogens, especially Candida auris, has underscored the need for effective antifungal vaccines. This commentary highlights recent advances in peptide-based vaccination using the SNAP (Spontaneous Nanoliposome Antigen Presentation) platform, focusing on the FM-SNAP vaccine, a bivalent liposomal formulation targeting the surface-expressed peptides fructose bisphosphate aldolase (Fba) and methionine synthase (Met6). Compared to earlier constructs such as MP12, FM-SNAP achieves superior immunogenicity and long-lasting protection at lower antigen doses. It elicits balanced Th1/Th2 cytokine responses and demonstrates durable efficacy in both immunocompetent and complement-deficient mouse models. The platform’s compatibility with clinically approved adjuvants (MPLA and QS-21), modular peptide design, and potential for multi-pathogen applications underscores its translational promise. FM-SNAP exemplifies a next-generation vaccine strategy that is both scalable and adaptable for high-risk immunocompromised populations.